Vaterite Dissolution: Mechanism and Kinetics - Milner, MP; Yang, M; Compton, RG (American Chemical Society, 2024)
The dissolution of porous spherulitic, vaterite particles in aqueous solution is investigated via microscopic monitoring of their size as a function of time. The latter is shown to provide a clear, generic distinction between dissolution controlled either by the rate of a surface-controlled reaction or via dissolution under conditions where the concentration of calcium and carbonate ions is pinned locally by the solubility product of vaterite followed by diffusion away from the dissolving interface into the bulk solution. Dissolution under “thermodynamic control” is shown to be the case for vaterite particles, allowing a value of the solubility product to be determined in the light of the known solution phase equilibria, including the ion pairs CaCO3, CaOH+, and CaHCO3 +.